2018
DOI: 10.1155/2018/2519375
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Transient Pupillary Light Reflex and Retinal Function Impairment in Patients with Retinitis Pigmentosa

Abstract: Purpose To investigate the relationship between transient pupillary light reflex (PLR) and visual function in patients with retinitis pigmentosa (RP). Methods A retrospective study was performed with 137 eyes of 73 patients with RP. Transient pupillary light reflex was measured by the vision monitor system (MonColor; Metrovision, France). Dark-adapted transient PLRs were elicited by four specific levels of stimulus luminance (−5, −3, −1, and 0 log cd/m2, blue or white light). Best-corrected visual acuity (BCVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Since the mice used in this model had a mutation in the melanopsin gene ( Opn4 −/− ) that canceled its photosensitive function, the responses obtained in this reflex after the injection of sodium iodate corresponded exclusively to the photoreceptors, and their decrease was a faithful reflection of the lesion they suffered [ 40 ]. The novelty of these experiments is that their results reinforce the correlation with pupillary reflex dysfunction observed in patients suffering from various retinal disorders [ 50 , 51 , 52 , 53 ]. However, further research would be required to discern the origin of this dysfunction.…”
Section: Discussionmentioning
confidence: 85%
“…Since the mice used in this model had a mutation in the melanopsin gene ( Opn4 −/− ) that canceled its photosensitive function, the responses obtained in this reflex after the injection of sodium iodate corresponded exclusively to the photoreceptors, and their decrease was a faithful reflection of the lesion they suffered [ 40 ]. The novelty of these experiments is that their results reinforce the correlation with pupillary reflex dysfunction observed in patients suffering from various retinal disorders [ 50 , 51 , 52 , 53 ]. However, further research would be required to discern the origin of this dysfunction.…”
Section: Discussionmentioning
confidence: 85%
“…Many studies suggest that chromatic pupillometry is more sensitive than standard visual electrophysiological examination for detecting retinal functional activity in the later stages of retinal degeneration ( Park et al, 2010 ; Jacobson et al, 2011 ; Kardon et al, 2011 ; Lisowska et al, 2017 ; Rukmini et al, 2019 ; Krishnan et al, 2020 ; Yamamoto et al, 2023 ). In previous work, we demonstrated that chromatic pupillometry can quantitatively estimate retinal function in RP patients ( He et al, 2018 ), and we used this method to evaluate the therapeutic effect of stem cell transplantation in clinical trials ( Liu et al, 2017 ). Additionally, we found that high-intensity blue light can induce pupillary responses that are not easily attenuated ( Zhang et al, 2021 ), even in patients with NLP.…”
Section: Introductionmentioning
confidence: 99%
“…One of less noticed in this regard is changes in pupillary dynamic responses while providing different stimuli. Limited studies have provided these characteristics in different eye conditions including amblyopic patients, ( 14 ) people with multiple sclerosis, ( 15 ) people with diabetic retinopathy, ( 16 ) people with retinitis pigmentosa, ( 17 ) and finally while reducing or increasing accommodation ( 10 ). However, a review of available studies shows that evaluation of dynamic pupil changes after near ocular work has not been performed yet.…”
Section: Introductionmentioning
confidence: 99%